VARIABILITAS KUALITAS KAYU MAHANG (Macaranga hypoleuca) DARI KALIMANTAN TENGAH (Variability of Macaranga hypoleuca Timber Quality From Central Kalimantan): M. Damiri dan Yanciluk - JHT, Admin (Jurnal Hutan Tropika, 2015)
ABSTRACTMahang (Macaranga hypoleuca) is one of some lesser know species that widely grow at the secondary forest, especially in Central Kalimantan. This research was aimed to determine the properties of mahang timber quality and the relationship between axial and radial position concerning its properties. Research method using the factorial complete random design (CRD) 3 x 2. The first factor is the axial wood position (a) consist of the bottom (a1), the middle (a2), and the top (a3). The second factor is radial position (b) consist of axial (b1), and radial (b2). Data analysis using honestly significant difference (HSD). The wood’s water content test using ISO 3130 – 1975 (E) standart, the wood density test using ISO 3131 – 1975 (E) standart, and the wood shrinkage test using ISO/DIS 4469. The cell proportion test using grid mask method of Image Pro Plus V 4.5 program, whereas its dimension test using Image Pro Plus V 4.5 program. The wood extractive content test using ASTM D.2016-65, (ASTM D.1107-56), and (ASTM D.1110-56) procedures. Research result showed that wet vapor is 44.43%, dry vapor is 13.46%, specific gravity is 0.36, and the shrinkage TR ratio is 1.76. About fiber dimension: the fiber length is 1.6 mm, fiber diameter is 18.5µ, lumen diameter is 15.2 µ and thick of cell wall is 3.3 µ. The proportion of wood cell: spokes cell is 10.5%, parenkim is 11.3%, vessel cell is 16.5% and fiber is 62.1%. There is a relationship between several adhessiveness characteristics and wood quality toward the influences of the mahang wood’s actial and radial positions.Keywords: axial, Macaranga hypoleuca, radial, wood quality